USING ICT AS AN EFL CLASSROOM TOOL: BENEFITS AND CHALLENGES (Innovate Conferences, 2025)
There have been a number of research studies regarding information and communication technologies in EFL classrooms and their new methods. While new implementations are suggested to support ICT-based teaching, EFL teachers must be trained on how to use them properly in teaching English. To identify the perceptions of EFL teachers and their awareness of ICT in teaching, a number of studies showed that most teachers were highly motivated to utilize ICT as it helps teachers to make their lessons more enjoyable and effective (Warshaw, 1989), which supports English learners to learn English communicatively without stress. Although ICT-based teaching is regarded as useful to improve learners’ language skills and inspire them to be active, creative and passion, it leads to lots of difficulties and barriers which most EFL teachers experience in incorporating ICT in their language classroom. Growing concerns without concrete objectives, plans and lack of ICT awareness will cause teachers and professors to use them improperly and waste of effort and time.